Experimental study on mechanical properties of double-layer damped liquid storage tanks with various isolation devices - Xiang Li; Lei Xu; Fa Yang; Li-jie Zhu; Bo-lin Wang; Zheng Lu (Soil Dynamics and Earthquake Engineering, 2026)

Hierarchical core–shell nanoplatforms based on sacrificial template-directed ZnO2@ZIF-8 for spatiotemporally controlled and self-augmented chemodynamic–photothermal antibacterial therapy - Yi-Fei Hui; Duan-Ping Hu; Yi Zhao; Shulin Li; Zhi-Feng Cai; Lin-Yi Li; Yuming Xie; Yong-Nian Zeng; Zu-Jin Lin; Fa-Qiang Tang (Chemical Engineering Journal, 2026)

S-scheme Cu-BTC/CuWO4 heterojunction for simultaneous harmful marine algal inactivation and toxin reduction: An ecologically safe restoration strategy - Jie Zhang; Fa'e Dao; Mingcan Wu; Wanchun Guan; Shu Lin; Kezhen Qi (Chemical Engineering Journal, 2026)

Multi-site Ag-π conductive gel for ultrasensitive digital acousto-optic sensor - Jintao Tian; Yihao He; Hao-Ran Yang; Xing Han; Xiao-Wen Sun; Hong Yao; Tai-Bao Wei; Jin-Fa Chen; Bingbing Shi; Qi Lin (Chemical Engineering Journal, 2026)

Interannual variability of secondary organic carbon driven by seasonal shifts in formation regimes in southern Taiwan - Jun-Fa Ye; Chih-Yu Chan; Jian-Xian Wu; Shi-Ya Tang; Tse-Lun Chen; Li-Hao Young; Yu-Chieh Ting; Yen-Ping Peng; Wei-Hsiang Chen; Ming-Yeng Lin; Si-Chee Tsay; Neng-Huei Lin; et al. (Atmospheric Environment, 2026)

Asymmetric coordination configuration unlocks single-atom nanozyme catalytic activity for redox-immune homeostasis and temporomandibular joint osteoarthritis therapy via macrophage depolarization and cGAS-STING pathway inhibition - Kaixun He; Hanyu Lin; Penghui Wei; Hongjia Zheng; Zhonghan Chen; Sihui Zhang; Yanjing Ou; Wenting Jiang; Wenxiu Yuan; Geyuan Zheng; Jiang Chen; Yi Zuo; et al. (Chemical Engineering Journal, 2026)

S-methoprene affected the population growth of Ephestia elutella (Hübner) - Lin-chong An; Xiao-fei Yu; Si-qi Wan; Mao-fa Yang (Journal of Stored Products Research, 2026)

Agricultural landscapes supporting conservation planning: Spatial prioritization of conservation areas for farmland birds - Luu Van Thong Trac; Chen-Fa Wu; Chien-Ying Lin (Ecological Modelling, 2026)

Maternal PAN2 selectively maintains mRNA Poly(A) tail homeostasis to regulate RNA degradation during oocyte-to-early embryo transition in mice - Xuan Wu; Hua Zhang; Yu-Ke Wu; Zhuo-Yue Niu; Jing-Wen Liu; Lu Chen; Jia-Jia Cao; Yu-Lin Chen; Shu-Yan Ji; Fa-Long Lu; Heng-Yu Fan (Science Bulletin, 2026)

Source-specific VOCs and atmospheric oxidation capacity drive the formation of secondary aerosols and visibility impairment in East Asia suburban environments - Tse-Lun Chen; Kuan-Chieh Lee; Jun-Fa Yeh; Jian-Xian Wu; Li-Hao Young; Neng-Huei Lin; Si-Chee Tsay; Wen-Yinn Lin; Chia-Hsin Lin; Ta-Chih Hsiao (Journal of Hazardous Materials, 2026)

Effects of exogenous N-acyl-homoserine lactones on biofilm formation by denitrifying bacteria and denitrification start-up in sequencing batch biofilm reactors - Zhi-fei Li; Meng-yuan Yu; Jun-lin Li; Jun Xie; Xiang-ju Cheng; Wang-bao Gong; Kai Zhang; Guang-jun Wang; Yun Xia; Wen-ping Xie; Quan-fa Zhong; Hong-yan Li; et al. (Journal of Environmental Chemical Engineering, 2026)

Chronic exposure to low-dose cadmium disrupts spermatogenesis in mice through ectoplasmic specialization damage - Yue Li; Zi-Fa Li; Bo Qiu; Kai Chen; Tian-Lin Zhang; Hai-Peng Wang; Lin Wang (Journal of Environmental Sciences, 2026)

Near-Surface Q-Factor Estimation Using a Non-Gaussian Energy Spectrum - Ze-lin Li; Jiang-nan Tong; Ya-nan Jiang; Tong Chen; Guo-fa Li (Applied Geophysics, 2026)

Opisoma menchikoffi Dubar, 1948: New occurrences from the Lower Jurassic of the High Atlas, Morocco and Tethyan Himalaya, southern Xizang (Tibet), China - Fu-Lin Li; Kai Ye; Xin Rao; Zhong Han; Cheng-Gang Wang; Xiong-Wei Zeng; Long Wang; Hao Liu; Zong-Xin Wang; Fa-Fu Wu; Kun Liang; Wen-Kun Qie (Palaeoworld, 2026)

Ultrasonic-vacuum combined effects on Antarctic krill oil oxidation stability: Potential mechanisms of oxygen reduction and influence on reverse micelle - Xue-Chen Pei; Fa-Wen Yin; Chang-Qiang Leng; Xin-Miao Wang; Qian Wang; Hui-Lin Liu; Bei-Wei Zhu; Da-Yong Zhou (Food Chemistry, 2026)

Geophysical Characteristics and Prospecting Significance of the Halong’erma Polymetallic Deposit in the East Kunlun Metallogenic Belt - You Zhou; Zhi-Qiang Zhang; Ji-En Dong; Hai-Yue Fu; Fa-Long Qi; Wen-ke Fan; Hao Ren; Xue-lin Huang (Applied Geophysics, 2025)

Population structure of Tachypleus tridentatus in Xiamen Bay: Proposing a network of transboundary marine protected areas - Yi-Hua Jin; Yi-Jia Shih; Hsin-I. Lin; Ya-Hui Chen; Yung-Sheng Cheng; Chia-Fa Lee; Yang-Chi Chang; Yi Chang (Regional Studies in Marine Science, 2025)

Quantification of the variability of the soil moisture field in response to variations in the rainfall field - Ching-Min Chang; Chuen-Fa Ni; Chi-Ping Lin; I-Hsian Lee; Wei-Cheng Lo (Journal of Hydrology, 2025)

Multi-side-port nanotube array based on pillar[5]arene-Ag(I) self-assembly for efficient and recyclable separation of trace pyridine - Hao-Ran Yang; Jintao Tian; Xing Han; Tai-Bao Wei; Hong Yao; Bingbing Shi; Jin-Fa Chen; Qi Lin (Chemical Engineering Journal, 2025)

Reconciling volume- and mass-based hygroscopicity parameters: Insights from coupled H-TDMA–APM measurements - Ta-Chih Hsiao; Ke-Ching Chen; Jun-Fa Ye; Si-Chee Tsay; Neng-Huei Lin (Atmospheric Environment, 2025)

Correction: Severe enterovirus A71 pathogenesis and immune responses in human nucleolin transgenic mice - Nien-En Hsiao; Ya-Fang Wang; Yi-Chen Lin; Wei-Ting Chou; Li-Jin Hsu; Shih-Min Wang; Jen-Ren Wang; Ming-Derg Lai; Shun-Hua Chen; Chuan-Fa Chang (Medical Microbiology and Immunology, 2025)

Severe enterovirus A71 pathogenesis and immune responses in human nucleolin transgenic mice - Nien-En Hsiao; Ya-Fang Wang; Yi-Chen Lin; Wei-Ting Chou; Li-Jin Hsu; Shih-Min Wang; Jen-Ren Wang; Ming-Derg Lai; Shun-Hua Chen; Chuan-Fa Chang (Medical Microbiology and Immunology, 2025)

Characterization of temporal nonstationary random soil moisture perturbation fields - Ching-Min Chang; Chuen-Fa Ni; Chi-Ping Lin; I-Hsian Lee; Wei-Cheng Lo (Advances in Water Resources, 2025)

Novel fused-bimacrocycles supply stepwise and orthogonal assembly, versatile way to construct multi-functional materials - Ting-Ting Huang; Xin-Yu Dai; Juan Liu; Tai-Bao Wei; Hong Yao; Bingbing Shi; Jin-Fa Chen; Qi Lin (Chemical Engineering Journal, 2025)

Sugar-based block copolymer/carbon nanotube nanocomposites for thermoelectric applications - Yen-Yu Chen; Hong Li; Chih-Jung Lin; Koshin Tanaka; Meng-Hao Lin; Shao-Huan Hong; Min-Chi Fu; Jian-Fa Ding; Yu-Jane Sheng; Redouane Borsali; Tsuyohiko Fujigaya; Cheng-Liang Liu (Chemical Engineering Journal, 2025)

Targeting neuroblastoma with 3β,5α-tetrahydrocorticosterone: Activation of aryl hydrocarbon receptor inhibits tumor growth, metastasis, and stemness while promoting neural differentiation - Zhu-Qian Wen; Wen-Ming Hsu; Chien-Chun Chiou; Farhan Azhwin Maulana; Chia-Hwa Chang; Jie-Ming Huang; Zhi-Kai Yu; Chien-Chin Chen; Neng-Yu Lin; Chun-FA. Tsai; Jheng-Siou Lai; Yue-Ling Chen; et al. (Chemico-Biological Interactions, 2025)

Integration of critical state theory into a micromechanical model for granular materials accounting for fabric evolution - Hai-Lin Wang; Xiaoqiang Gu; Zhen-Yu Yin; Chao-Fa Zhao (Computers and Geotechnics, 2025)

System temperature prediction and verification of all-sky electrostatic analyzer on the lunar surface - Tsung-Pin Hung; Chih-Yu Chiang; Tzu-Fang Chang; Zhao-Yu Huang; Yu-Rong Cheng; Sheng-Cheng Tsai; Tzu-En Yen; Jih-Run Tsai; Shin-Fa Lin (Advances in Space Research, 2025)

Antimony induces mitochondria-dependent and ER stress-triggered apoptosis via the oxidative stress-activated JNK signaling pathway in pancreatic islet β-cells - Ken-An Lin; Chin-Chuan Su; Shing-Hwa Liu; Kuan-I. Lee; Kai-Min Fang; Chih-Hsin Tang; Chun-Ying Kuo; Kai-Chih Chang; Jun-An Ke; Chun-Fa Huang; Ya-Wen Chen; Ching-Yao Yang (Toxicology, 2025)

Vanadium-cobalt oxide nanoflower catalyst for efficient and stable overall water splitting in alkaline and seawater electrolytes - Yong-qi Tian; Song-lin Xu; Jia Li; Shuang-shuang Zhang; Bo-yao Zhang; Rong-da Zhao; Fu-fa Wu; De-peng Zhao (Next Research, 2025)

Aggregation pheromones of Bostrichidae: A review - Li Yu; Xiao-Lu Cao; Wei Zheng; Jun Li; Fa-Yang Xie; Xia-Lin Zheng (Journal of Stored Products Research, 2025)

Bipolar membrane electrodialysis for producing acid and alkali from concentrated seawater: Industrial application in Bohai Sea, China - Jia-Wang Qin; Shun Tang; Jia-Lin Shi; Teng-Fei Zhang; Lu Yang; Fang Wang; Liang Yin; Yuan-Fa Zhuang (Journal of Water Process Engineering, 2025)

Real-time assessment of PM1.0-bound trace metal cancer risk through high-resolution GED-ICP-MS and integrated ELCR analysis - Li-Ti Chou; Yi-Pin Lin; Chia-Hung Yu; Jun-Fa Ye; Wen-Che Hou; Ta-Chih Hsiao (Journal of Hazardous Materials, 2025)

Integrating synergistic effects of biodiversity conservation and ecosystem services into nature conservation strategies - Luu Van Thong Trac; Da-Li Lin; Chen-Fa Wu (Journal of Environmental Management, 2025)

Revealing the oxidation mechanism of Antarctic krill oil induced by metal ion: Focusing on the influence of reverse micelles - Xue-Chen Pei; Fa-Wen Yin; Meng-Ling Jin; Xin-Miao Wang; Hui-Lin Liu; Liang Song; Bei-Wei Zhu; Da-Yong Zhou (Food Chemistry, 2025)

Evaluation of the efficacy and safety of omega-3 fatty acid nutritional supplements from Schizochytrium sp. in dog food - Zi-Xu Zhang; Yan-Cheng Lin; Min Lian; Ying-Feng Li; Jin-Fa Chen; Xue-Lian Ma; Dong-Sheng Guo; Guang Yang; Xiao-Man Sun (Algal Research, 2025)

Mechanistic insights into endometriosis: roles of Streptococcus agalactiae and L-carnitine in lesion development and angiogenesis - Yuan Zhuang; Ting Lyu; Yang Chen; Wei Li; Lei Tang; Shi-ping Xian; Peng-fei Yang; Lijie Wang; Qian-qian Zhang; Chaoming Mei; Yu-jing Lin; Zhixiang Yan; et al. (Angiogenesis, 2025)

Manganese oxide and urea-assisted engineering of nickel-iron compounds for high-performance battery-supercapacitor hybrid devices - Shen-Fa Dong; Hamed Cheshideh; Chutima Kongvarhodom; Muhammad Saukani; Sibidou Yougbaré; Hung-Ming Chen; Yung-Fu Wu; Lu-Yin Lin (Journal of Environmental Chemical Engineering, 2025)

Study on mechanism behind browning of Antarctic krill upon hot air drying and its control - Chao Guo; Xiang-Bo Zeng; Bo Peng; Fa-Wen Yin; Hui-Lin Liu; Bei-Wei Zhu; Da-Yong Zhou (Food Chemistry, 2025)

Associations of exposure to arsenic species and endogenous sex hormones with oral cancer: a hospital-based study in Southeastern China - Na Wang; Wenting Zhang; Haoyuan Song; Weihai Huang; Fa Chen; Fengqiong Liu; Yulan Lin; Yu Qiu; Bin Shi; Lisong Lin; Jing Wang; Baochang He (Environmental Pollution, 2025)

Correction to: Comparison of Long‑Term Outcomes in Ruptured Diffuse Brain Arteriovenous Malformations Between Interventional Therapy and Conservative Management - Changyu Lu; Heze Han; Li Ma; Ruinan Li; Zhipeng Li; Haibin Zhang; Kexin Yuan; Yukun Zhang; Anqi Li; Ke Wang; Yang Zhao; Weitao Jin; et al. (Translational Stroke Research, 2025)

RNA-binding protein expression based machine learning model predicts metastasis and treatment outcome of testicular cancer - Lin-jian Mo; Hai-qi Liang; Zhen-yuan Yu; Yao-wen Liang; Chuan-xin Gu; Qiu-ju Wei; Qi-huan He; Fa-ye Wei; Ji-wen Cheng; Zeng-nan Mo (Genes & Genomics, 2025)

CTHRC1 expresses in cancer-associated fibroblasts and is associated with resistance to anti-androgen therapy in prostate cancer - Hai-qi Liang; Qi-huan He; Qiu-ju Wei; Qi-zhou Mo; Guang-lin Yang; Fa-ye Wei; Li-wei Wei; Yu-jian Li; Min Qin; Ji-wen Cheng (Genes & Genomics, 2025)

Dietary pyridoxine promoted muscle protein deposition relating to PI3K/AKT/TOR pathway and the ubiquitin proteasome system in grass carp (Ctenopharyngodon idella) - Li-Fu Gong; Xiao-Qiu Zhou; Lin Feng; Pei Wu; Wei-Dan Jiang; Yao-Bin Ma; Xiao-Wan Jin; Hong-Mei Ren; Jia-Yong Tang; Fa-Li Wu; Yang Liu (Food Bioscience, 2025)

Recurrence of Cerebral Arteriovenous Malformation Following Complete Obliteration Through Endovascular Embolization - Qiang Hao; Haibin Zhang; Heze Han; Hengwei Jin; Li Ma; Ruinan Li; Zhipeng Li; Anqi Li; Kexin Yuan; Qinghui Zhu; Ke Wang; Runting Li; et al. (Translational Stroke Research, 2025)

Rainfall Promote Bruceine D Release from Brucea javanica Leaf Litter Thus Reducing Weeds and Enhancing Plant Competitiveness - Yao Tong; Hai-Ou Lin; Dong-Qiang Zeng; Fa-Yang Xie; Wen-Wei Tang (Journal of Chemical Ecology, 2025)

The herbicide 2,4-dichlorophenoxyacetic acid induces pancreatic β-cell death via oxidative stress-activated AMPKα signal downstream-regulated apoptotic pathway - Ken-An Lin; Chin-Chuan Su; Kuan-I Lee; Shing-Hwa Liu; Kai-Min Fang; Chih-Hsin Tang; Wei-Cheng Lia; Chun-Ying Kuo; Kai-Chih Chang; Chun-Fa Huang; Ya-Wen Chen; Ching-Yao Yang (Toxicology Letters, 2025)

Spatial variability of groundwater flow fields caused by nonstationary random input parameter processes - Ching-Min Chang; Chuen-Fa Ni; Chi-Ping Lin; I-Hsian Lee (Journal of Hydrology, 2025)

Applying Fermatean fuzzy sets in sustainable development assessment: a case study in the wire and cable sector - Jung-Fa Tsai; Shih-Ping Shen; Ming-Hua Lin (Clean Technologies and Environmental Policy, 2025)

The change rule of lipid oxidation and hydrolysis driven via water in Antarctic krill oil: Based on association colloid formation - Xue-Chen Pei; Xiang-Bo Zeng; De-Yang Li; Xin-Miao Wang; Fa-Wen Yin; Hui-Lin Liu; Da-Yong Zhou (Food Chemistry, 2025)

Research progress of electrospinning in food field: A review - Fa-Lin Sun; Ming-Yue Zhao; Yue Li; Zhi-Ying Li; Xiu-Jun Li; Nuo Wang; Bo-Wen Hu; Hao-Yu Xue; Min Zhao; Jin-Long Tian (Food Hydrocolloids, 2025)

A multirisk-rescued biomimetic nanozyme against periodontitis via inflammation targeting and microenvironment reprogramming - Lin Li; Rui-Xin Wu; Jia Wang; Rui Jin; Xin-Yu Zhang; Mei Xu; Si-Yao Li; Rui Gao; Bei-Min Tian; Xiao-Tao He; Fa-Ming Chen; Yuan Yin (Chemical Engineering Journal, 2025)

Mitochondria-targeted delivery of zinc-coordinated resveratrol nanoparticles rescues the osteogenic potential of periodontal ligament stem cells compromised by inflammation for periodontal wound healing - Yu-Jie Tan; Xuan Li; Wen-Jie Zhang; Yu-Meng Cao; Jie-Kang Zou; Lin Jing; Dian Gan; Yu-Zhe Chen; Mei Xu; Ying An; Fa-Ming Chen; Xiao-Tao He; et al. (Chemical Engineering Journal, 2025)

Forms of rare earth loss and the function mechanism of acetic acid in the aluminum removal process of rare earth leaching liquor - Chen Xin; Chen Jin-fa; Xiao Xin-lei; Fan Lin; Xiao Yan-fei; Huang Li (Minerals Engineering, 2024)

Comparison of Long-Term Outcomes in Ruptured Diffuse Brain Arteriovenous Malformations Between Interventional Therapy and Conservative Management - Changyu Lu; Heze Han; Li Ma; Ruinan Li; Zhipeng Li; Haibin Zhang; Kexin Yuan; Yukun Zhang; Anqi Li; Ke Wang; Yang Zhao; Weitao Jin; et al. (Translational Stroke Research, 2024)

Risk of New-onset Stroke in Patients with Type 2 Diabetes with Chronic Kidney Disease on Sodium-glucose Co-transporter-2 Inhibitor Users - Gwo-Ping Jong; Tsung-Kun Lin; Pei-Lun Liao; Jing-Yang Huang; Tsung-Yuan Yang; Lung-Fa Pan (Translational Stroke Research, 2024)
Clinical studies have investigated the effects of using sodium-glucose co-transporter-2 (SGLT2) inhibitors on the development of new-onset stroke (NOS) in patients with type 2 diabetes (T2D) and chronic kidney disease (CKD), but the findings are inconsistent. This study aimed to examine the association between the use of SGLT2 inhibitors and NOS risk in patients with T2D and CKD. We conducted a nationwide retrospective cohort study using data from the Taiwan Health Insurance Review and Assessment Service database for the years 2004 to 2019. The primary outcome was the risk of incident stroke, which was estimated using hazard ratios (HRs) and 95% confidence intervals (CIs). We used multiple Cox regression modeling to analyze the association between SGLT2 inhibitor use and the risk of stroke in patients with T2D and CKD. In a cohort of 113,710 patients with T2D and CKD who were using SGLT2 inhibitors and 227,420 patients with T2D and CKD who were not using SGLT2 inhibitors, after applying a 1:2 sex- and age-matching strategy, 2,842 and 7,169 NOS events were recorded, respectively. The event rate per 10,000 person-months was 10.60 (95% CI 10.21 to 11.03) for SGLT2 inhibitor users and 13.71 (13.39–14.03) for non-SGLT2 inhibitor users. After adjusting for the index year, sex, age, comorbidities, and concurrent medication, there was a decreased risk of NOS for SGLT2 inhibitor users (adjusted HR 0.80; 95% CI 0.77–0.84) compared with non-SGLT2 inhibitor users. The sensitivity test for the propensity score 1:1-matched analyses showed similar results (adjusted HR 0.80; 95% CI 0.76–0.84). The type of SGLT2 inhibitor subgroup analysis for incident stroke showed consistent results. We concluded that the use of SGLT2 inhibitors in patients with T2D and CKD was associated with significantly low rates of NOS. The significantly low rates of NOS in patients with T2D and CKD were greater among females and less than 50 years patients.

Cyanide content, nutrient composition, physicochemical properties and sensory quality of flaxseed oil bodies prepared from flaxseeds (Linum usitatissimum L.) treated with different heat treatment methods - Rui Zheng; Hui-Lin Liu; Nan-Nan Cui; Jun-Zhuo Zhou; Xin Sun; Fa-Wen Yin; Da-Yong Zhou (Food Research International, 2024)

Mechanism of discoloration of Antarctic krill oil upon storage: A study based on model systems - Xiang-Bo Zeng; Xue-Chen Pei; De-Yang Li; Fa-Wen Yin; Hui-Lin Liu; Meng-Ling Jin; Jiang-Hua Zhang; Da-Yong Zhou (Food Chemistry, 2024)

Comparative study on the morphological characteristics, nutritional quality, and tastes of large yellow croaker from five cage culture areas: Relay farming improved fish quality - Jia-Lang Zheng; Fa-Guo Wan; Yong-Long Chen; Li-Hua Jiang; Qing-Hao Zhan; Tian-Hong Chen; Shun Chen; Qing-Lin Zhu; Wei-Ye Li; Yi-Fan Liu; Wei-Hua Song; Xiao-Jun Yan (Aquaculture, 2024)

Analytical behavior of concrete-filled steel tubular pile used in coastal wharf structure subjected to combined loads - Lan Lin; Fa-cheng Wang (Ocean Engineering, 2024)

CA1 Modulates the Osteogenic Differentiation of Dental Follicle Stem Cells by Activating the BMP Signaling Pathway In Vitro - Jin-ze Zhao; Ying-Ying Ge; Ling-fa Xue; Yao-xiang Xu; Jin Yue; Cong Li; Wen-lin Xiao (Tissue Engineering and Regenerative Medicine, 2024)

Niche convergence and biogeographic history shape elevational tree community assembly in a subtropical mountain forest - Liang-Liang Ma; Sebastian Seibold; Marc W. Cadotte; Jia-Yun Zou; Jie Song; Zhi-Qiong Mo; Shao-Lin Tan; Lin-Jiang Ye; Wei Zheng; Kevin S. Burgess; Zhi-Fa Chen; De-Tuan Liu; et al. (Science of The Total Environment, 2024)

Characterization of a pangolin SARS-CoV-2-related virus isolate that uses the human ACE2 receptor - Luo-Yuan Xia; Xue-Feng Wang; Xiao-Ming Cui; Yi-Ming Zhang; Zhen-Fei Wang; En-Tao Li; Chang-Fa Fan; Ke Song; Yuan-Guo Li; Run-Ze Ye; Fang-Xu Li; Dai-Yun Zhu; et al. (Science China Life Sciences, 2024)

Mechanism of color change in Antarctic krill oil during storage - Xiang-Bo Zeng; Fa-Wen Yin; Guan-Hua Zhao; Chao Guo; De-Yang Li; Hui-Lin Liu; Lei Qin; Fereidoon Shahidi; Da-Yong Zhou (Food Chemistry, 2024)

The effects of repeated freezing and thawing on bovine sperm morphometry and function - Chang-Guo Min; Xin Ma; Yu-Chan Wang; Cheng-Kun Zhong; Chong-shan Yuan; Kai-Yan Zhang; Cheng-Lin Zhan; Sheng-Kui Hou; Xin-Hai Wang; Jun Wang; Jing Zhao; Yi Fang; et al. (Cryobiology, 2024)

Co-pyrolysis of saw dust and oily sludge with waste-heat utilization of steel slag on rotary kiln simulated engineering practice - Hongdi Yu; Fawei Lin; Xuan Guo; Hongyun Yao; Fa Zheng; Jiantao Li; Meng Zhang; Rundong Li; Beibei Yan; Guanyi Chen (Fuel, 2024)

On the brink of explosion? Identifying the source and potential spread of introduced Zosterops white-eyes in North America - Devon A. DeRaad; Marlon E. Cobos; Natalie R. Hofmeister; Lucas H. DeCicco; Madhvi X. Venkatraman; Isao Nishiumi; Bailey McKay; Fa-Sheng Zou; Kazuto Kawakami; Chang-Hoe Kim; Ruey-Shing Lin; Cheng-Te Yao; et al. (Biological Invasions, 2024)

Stochastic Quantification of Spatial Variability of Flow Fields in Heterogeneous, Non-uniform, Confined Aquifers - Chuen-Fa Ni; Ching-Min Chang; Chi-Ping Lin; I-Hsian Lee (Transport in Porous Media, 2024)

Variability in the displacement of solute particles in heterogeneous confined aquifers - Ching-Min Chang; Chuen-Fa Ni; Chi-Ping Lin; I-Hsian Lee (Advances in Water Resources, 2024)

Examination of the effects of triacylglycerol lipase on astaxanthin conversion in the black tiger prawn Penaeus monodon - Xin-Tao Li; Li-Shi Yang; Shi-Gui Jiang; Qi-Bin Yang; Song Jiang; Fa-Lin Zhou; Yun-Dong Li; Jian-Zhi Shi; Xu Chen; Yu-kai Yang; Jian-Hua Huang (Aquaculture, 2024)

3D network of zinc powder woven into fibre filaments for dendrite-free zinc battery anodes - Lin Sha; Bin-Bin Sui; Peng-Fei Wang; Zhe Gong; Yu-Hang Zhang; Yu-Han Wu; Li-Na Zhao; Jun-Jie Tang; Fa-Nian Shi (Chemical Engineering Journal, 2024)

Effective degradation of zearalenone by dye-decolorizing peroxidases from Pleurotus ostreatus and its metabolic pathway and toxicity analysis - Shuai Ding; Chen Lin; Qiuyun Xiao; Fa Feng; Junfeng Wang; Xing Zhang; Shengjing Yang; Lingling Li; Fei Li (Science of The Total Environment, 2024)

Technological diversity in the tropical-subtropical zone of Southwest China during the terminal Pleistocene: excavations at Fodongdi Cave - Fa-Xiang Huan; Shi-Xia Yang; Feng Gao; Xin-Ying Zhou; Jian-Ping Yue; Yu-Xiu Zhang; Jin-Xu Wu; Qi-Jun Ruan; Kai-Wei Qiu; Jing-wen Xu; Nai-Ru Lin; Yi-Ren Wang; et al. (Archaeological and Anthropological Sciences, 2024)

Induced differentiation of primordial germ cell like cells from SOX9+ porcine skin derived stem cells - Geng Zhang; Xin-Xiang Xie; Shu-Er Zhang; Fa-Li Zhang; Chun-Xiao Li; Tian Qiao; Paul W. Dyce; Xin-Lei Feng; Wei-Bo Lin; Qi-Cheng Sun; Wei Shen; Shun-Feng Cheng (Theriogenology, 2023)

Eudesmane-type sesquiterpenoids from the aerial parts of Artemisia lavandulaefolia and their anti-pancreatic cancer activities - Lin-Fen Ding; Guo-Xian Hu; Yu-Yao Liu; Qiu-Hua Wang; Zhang-Juan Li; Meng-Xia Shen; Gui-Fa Zhu; Xing-De Wu; Jia Su (Phytochemistry, 2023)

Ecosystem responses dominate the trends of annual gross primary productivity over terrestrial ecosystems of China during 2000–2020 - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Hua Qi; Meng Yang; Zhao-Gang Liu; Xiao-Jun Dou; Le-Xin Ma; Shi-Ping Chen; et al. (Agricultural and Forest Meteorology, 2023)

Variability of travel time of solute particles in single fractures with spatially variable aperture - Ching-Min Chang; Chuen-Fa Ni; Chi-Ping Lin; I-Hsian Lee (Engineering Geology, 2023)

SHARAD study on the structures and permittivity of a buried impact crater in Martian Central Elysium Planitia - Peng Fang; Wenzhe Fa; Jinhai Zhang; Yangting Lin (Science China Earth Sciences, 2023)

First transcriptome profiling in gill and hepatopancrease tissues of Metapenaeus ensis in response to acute ammonia-N stress - Yun-Dong Li; Meng-Ru Si; Shi-Gui Jiang; Qi-Bin Yang; Song Jiang; Li-Shi Yang; Jian-Hua Huang; Fa-Lin Zhou (Fish & Shellfish Immunology, 2023)

A green synthesized medicine residue carbon-based iron composite for the removal of chromium (VI) and cadmium (II): Performance, kinetics and mechanism - Fa-Ming Diao; Man-Li Chen; Lin-Yin Tong; Ying-Nan Chen; Zeng-Hui Diao (Environmental Science and Pollution Research, 2023)

Investigation of analytical behavior of concrete filled steel tubular (CFST) offshore rock-socketed pile under lateral load - Lan Lin; Fa-cheng Wang (Ocean Engineering, 2023)

Long-term DEHP/MEHP exposure promotes colorectal cancer stemness associated with glycosylation alterations - Pei-Chun Shih; Hsin-Pao Chen; Ching-Cheng Hsu; Chung-Hsien Lin; Chou-Yuan Ko; Chao-Wen Hsueh; Cheng-Yi Huang; Tian-Huei Chu; Cheng-Chun Wu; Yu-Cheng Ho; Ngoc Uyen Nhi Nguyen; Shih-Chung Huang; et al. (Environmental Pollution, 2023)

Short- and medium-chain chlorinated paraffins in urban road dust of Shanghai, China: concentrations, source apportionment and human exposure assessment - Xue-Tong Wang; Cheng-Lin Wang; Ying Zhou; Guo-Fa Ren; Rui Fu; Jing An (Environmental Geochemistry and Health, 2023)

Effect of Tyrosol Acyl Esters on the Antioxidant Status of Mussel ( Mytilus edulis ) Oil During Accelerated Oxidative Storage - Qian Wang; Mo-Tong Zhang; Xin-Miao Wang; Guan-Hua Zhao; Yuan-Yuan Hu; Fa-Wen Yin; Hui-Lin Liu; Xiao-Yang Liu; Da-Yong Zhou (Journal of Aquatic Food Product Technology, 2023)

Isoquinoline alkaloids from Corydalis edulis Maxim. Exhibiting insulinotropic action - Zhi-Tian Peng; Hui-Xia Huo; Ling-Hui Chao; Yue-Lin Song; Di-Fa Liu; Zhang-Wei Wang; Yuan Zhang; Yun-Fang Zhao; Peng-Fei Tu; Jiao Zheng; Jun Li (Phytochemistry, 2023)

Glyphosate-induced autophagy inhibition results in hepatic steatosis via mediating epigenetic reprogramming of PPARα in roosters - Cai-Yu Lian; Sheng Wei; Zi-Fa Li; Shu-Hui Zhang; Zhen-Yong Wang; Lin Wang (Environmental Pollution, 2023)

A 90-Day Prognostic Model Based on the Early Brain Injury Indicators after Aneurysmal Subarachnoid Hemorrhage: the TAPS Score - Runting Li; Fa Lin; Yu Chen; Junlin Lu; Heze Han; Li Ma; Yahui Zhao; Debin Yan; Ruinan Li; Jun Yang; Shihao He; Zhipeng Li; et al. (Translational Stroke Research, 2023)

Anisotropic creep behavior of soft-hard interbedded rock masses based on 3D printing and digital imaging correlation technology - Yun Tian; Fa-quan Wu; Hong-ming Tian; Zhe Li; Xiao-yun Shu; Lin-kai He; Man Huang; Wei-zhong Chen (Journal of Mountain Science, 2023)

The diversity of mycorrhiza‐associated fungi and trees shapes subtropical mountain forest ecosystem functioning - Ya‐Huang Luo; Liang‐Liang Ma; Sebastian Seibold; Marc W. Cadotte; Kevin S. Burgess; Shao‐Lin Tan; Lin‐Jiang Ye; Wei Zheng; Jia‐Yun Zou; Zhi‐Fa Chen; De‐Tuan Liu; Guang‐Fu Zhu; et al. (Journal of Biogeography, 2023)
Aim Mycorrhiza play key roles for ecosystem structure and functioning in forests. However, how different mycorrhizal types influence mountain forest biodiversity–ecosystem functioning (BEF) relationships are largely unknown. We evaluate how the diversity of distinct mycorrhiza‐associated fungi and trees shapes forest carbon storage along elevational gradients. Location Gaoligong Mountains within Hengduan Mountains, Southwest China. Taxon Seed plants and mycorrhizal fungi. Methods We used the data from 31 subtropical forest plots along elevational gradients on two aspects (east and west) of the mountain. We quantified species richness of trees and symbiotic fungi and assigned both to their mycorrhizal type (arbuscular mycorrhiza [AM], ectomycorrhiza [EcM] and ericoid mycorrhiza [ErM]). We then examined the diversity effects of mycorrhiza‐associated fungi and trees on above‐ground carbon stored in trees and organic carbon stored in soils. Results Species richness was highest for AM trees (79.5%), followed by ErM trees (13.4%) and then EcM trees (7.1%). Species richness of AM‐associated trees and fungi decreased with increasing elevation, while ErM‐associated trees and fungi showed an opposite trend. EcM‐associated diversity followed a hump‐shaped relationship with elevation. Positive relationships between diversity and above‐ground carbon were detected in all three mycorrhizal associations, but despite low species number, canopy‐dominating EcM trees comprised 64.4% of the amount of above‐ground carbon. Furthermore, community‐weighted means of height exhibited positive correlations with forest above‐ground carbon, indicating that positive selection effects occur. Soil organic carbon was positively related to EcM‐associated fungi diversity, above‐ground carbon mass and soil nitrogen availability, with the latter having strongest direct effects. Main Conclusions The distributions of forest biodiversity and carbon storage can be modulated by distinct mycorrhizal fungi and trees. Moreover, future global changes (e.g. climate warming, intensifying nitrogen deposition) could alter the mycorrhizal‐mediated BEF relationships in mountain forests.

Highly selective monoclonal antibody-based fluorescence immunochromatographic assay for the detection of fenpropathrin in vegetable and fruit samples - Zi-Hong Xu; Jun-Kai Wang; Qiu-Xiong Ye; Lin-Feng Jiang; Hao Deng; Jun-Fa Liang; Run-Xi Chen; Wei Huang; Hong-Tao Lei; Zhen-Lin Xu; Lin Luo (Analytica Chimica Acta, 2023)

Chlorpyrifos induces neuronal cell death via both oxidative stress and Akt activation downstream-regulated CHOP-triggered apoptotic pathways - Jhe-Wei Lin; Shih-Chang Fu; Jui-Ming Liu; Shing-Hwa Liu; Kuan-I Lee; Kai-Min Fang; Ren-Jun Hsu; Chun-Fa Huang; Kun-Min Liu; Kai-Chih Chang; Chin-Chuan Su; Ya-Wen Chen (Toxicology in Vitro, 2023)

Mapping Chinese annual gross primary productivity with eddy covariance measurements and machine learning - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Shi-Ping Chen; Shao-Min Liu; Hui-Min Wang; Jun-Hua Yan; Jun-Lei Tan; Fa-Wei Zhang; et al. (Science of The Total Environment, 2023)

Wind erodibility indices of aeolian sandy soils impacted by different vegetation restoration: a case study from the Shannan valley of the Yarlung Zangbo River - Bao-jun Zhang; Dong-hong Xiong; Lin Liu; Yong-fa Tang (Journal of Mountain Science, 2022)

Stochastic analysis of the variability of groundwater flow fields in heterogeneous confined aquifers of variable thickness - Ching-Min Chang; Chuen-Fa Ni; We-Ci Li; Chi-Ping Lin; I-Hsian Lee (Stochastic Environmental Research and Risk Assessment, 2022)

Petrogenesis of Eocene mafic and felsic magmas in the New Caledonia ophiolite: geochemistry and geochronology constraints - Yang Xu; Chuan-Zhou Liu; Xue-Fa Shi; Wei Lin (International Geology Review, 2022)

High Levels of 25-OH-Vitamin D and Copper in Pregnant Women with Abnormal Glucose Challenge Test - Chien-Hua Chiang; Wan-Ju Kung; Chien-Hung Lee; Yeong-Hwa Zen; Cheng-Fa Lee; Hui-Ru Yang; Ching-Chiang Lin; Yeou-Lih Huang (Biological Trace Element Research, 2022)

Natural component plumbagin as a potential antibacterial agent against Streptococcus agalactiae infection - Ai‐Guo Huang; Lin‐Jun Su; Wei‐Hao He; Fa‐Li Zhang; Chao‐Shuai Wei; Ying‐Hui Wang (Journal of Fish Diseases, 2022)
Streptococcus agalactiae , also known as Group B Streptococcus (GBS), can infect humans, terrestrial animals and fish. The emergence of bacterial resistance of S. agalactiae to antibiotics leads to an urgent need of exploration of new antimicrobial agents. In the study, the antibacterial activity of natural component plumbagin (PLB) against S. agalactiae was investigated in vitro and in vivo. The results showed that the minimal inhibitory concentration (MIC) of PLB against S. agalactiae was 8 mg/L. The growth curve assay revealed that PLB could inhibit the growth of S. agalactiae . In addition, the time‐killing curve showed that S. agalactiae was killed almost completely by 2‐fold MIC of PLB within 12 h. Transmission electron microscopy results showed obvious severe morphological destruction and abnormal cells of S. agalactiae after treated with PLB. The pathogenicity of S. agalactiae to zebrafish was significantly decreased after preincubation with PLB for 2 h in vitro, further indicating the bactericidal activity of PLB. Interestingly, PLB could kill S. agalactiae without inducing resistance development. Furthermore, pretreatment and post‐treatment assays suggested that PLB also exhibited the antibacterial activity against S. agalactiae infection in vivo by effectively reducing the bacterial load and improving the survival rate of S. agalactiae ‐infected zebrafish. In summary, PLB had potent antibacterial activity against S. agalactiae in vitro and in vivo, and it could be an excellent antimicrobial candidate to prevent and control S. agalactiae infection.

Sterols and triterpenoids from Ganoderma lucidum and their reversal activities of tumor multidrug resistance - Min Wu; Cui-e Shen; Qiao-fa Lin; Jin-yi Zhong; Yan-fei Zhou; Ben-chen Liu; Jian-hua Xu; Zhi-qiang Zhang; Peng Li (Natural Product Research, 2022)

Occurrence, source apportionment, and carcinogenic risk assessment of polycyclic aromatic hydrocarbons in urban road dusts in Shanghai - Xue-Tong Wang; Rui Fu; Ying Zhou; Cheng-Lin Wang; Guo-Fa Ren; Xiao-Li Wang; Hui Li (Environmental Science and Pollution Research, 2021)

Correction to: 2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

Recycle of synthetic calcium fluoride and waste sulfuric acid to produce electronic grade hydrofluoric acid - Min-Fa Lin; Jhong-Lin Wu; Ken-Lin Chang; Wen-Jhy Lee; Chih-Ping Chang; Yung-Chang Lin; Po-Han Chen (Environmental Science and Pollution Research, 2021)

Crenobacter intestini sp. nov., Isolated from the Intestinal Tract of Konosirus punctatus - Song-Biao Shi; Jia-Fa Wu; Li-Fang Yang; Ming-Guo Jiang; Cai-Mi Gao; Cheng-Lin Jiang; Yi Jiang (Current Microbiology, 2021)

Delayed association of acute particulate matter 2.5 air pollution exposure with loss of complexity in cardiac rhythm dynamics: insight from detrended fluctuation analysis - Tsung-Ying Tsai; Li-Wei Lo; Shin-Huei Liu; Wen-Han Cheng; Yu-Hui Chou; Wei-Lun Lin; Yenn-Jiang Lin; Shih-Lin Chang; Yu-Feng Hu; Fa-Po Chung; Jo-Nan Liao; Tze-Fan Chao; et al. (Environmental Science and Pollution Research, 2021)

Injection route affects intra-articular hyaluronic acid distribution and clinical outcome in viscosupplementation treatment for knee osteoarthritis: a combined cadaver study and randomized clinical trial - Jun Xiao; Yong Hu; Lin Huang; Zhi-Fa Huang; Wei-Zhou Jiang; Yu-Qiang Luo; Meng-Yan Jia; Di Chen; Zhan-Jun Shi (Drug Delivery and Translational Research, 2021)

2020 taxonomic update for phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Daniela Alioto; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Simon J. Anthony; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Tomáš Bartonička; et al. (Archives of Virology, 2020)

Impact of prophylactic/preemptive donor lymphocyte infusion and intensified conditioning for relapsed/refractory leukemia: a real-world study - Yu Wang; Qi-Fa Liu; De-Pei Wu; Jing-Bo Wang; Xi Zhang; Heng-Xiang Wang; Feng Gao; Shun-Qing Wang; Zi-Min Sun; Jian Ouyang; Kai-Lin Xu; Su-Jun Gao; et al. (Science China Life Sciences, 2020)

Lactobacillus plantarum PS128 Ameliorated Visceral Hypersensitivity in Rats Through the Gut–Brain Axis - Yen-Wenn Liu; Yen-Po Wang; Hsu-Fang Yen; Pei-Yi Liu; Wen-Jian Tzeng; Chia-Fen Tsai; Han-Chieh Lin; Fa-Yauh Lee; One-Jang Jeng; Ching-Liang Lu; Ying-Chieh Tsai (Probiotics and Antimicrobial Proteins, 2020)

The crucial role of bacterial laccases in the bioremediation of petroleum hydrocarbons - Yan Zhang; Dong-Fa Lin; Jun Hao; Zhi-Hao Zhao; Ying-Jiu Zhang (World Journal of Microbiology and Biotechnology, 2020)

Comparative analysis and natural evolution of squalene epoxidase in three Fritillaria species - Xu Lu; Lin-Ning Zhang; Jin-Fa Du; Xiao-Yan Zheng; Hui-Jun Li; Ping Li; Gui-Zhong Xin; Yan Jiang (Plant Molecular Biology, 2020)

New insights into antimetastatic signaling pathways of melatonin in skeletomuscular sarcoma of childhood and adolescence - Ko-Hsiu Lu; Chiao-Wen Lin; Yi-Hsien Hsieh; Shih-Chi Su; Russel J. Reiter; Shun-Fa Yang (Cancer and Metastasis Reviews, 2020)

Therapeutic Efficacy of Subcutaneous and Intraperitoneal Injections of a Single Dose of Human Umbilical Mesenchymal Stem Cells in Acute and Chronic Colitis in a Mouse Model - Yu-Lung Chang; Huei-Yu Lo; Shun-Ping Cheng; Kuo-Ting Chang; Xiu-Fang Lin; Sheng-Ping Lee; Jason Ma; Ming-Ling Kuo; Ming-Fa Hsieh; Chin-Kan Chan (Journal of Medical and Biological Engineering, 2020)

Mutational signatures and mutagenic impacts associated with betel quid chewing in oral squamous cell carcinoma - Shih-Chi Su; Lun-Ching Chang; Chiao-Wen Lin; Mu-Kuan Chen; Chun-Ping Yu; Wen-Hung Chung; Shun-Fa Yang (Human Genetics, 2019)

Pathological and therapeutic aspects of matrix metalloproteinases: implications in childhood leukemia - Yi-Hsuan Hsiao; Shih-Chi Su; Chiao-Wen Lin; Yu-Hua Chao; Wei-En Yang; Shun-Fa Yang (Cancer and Metastasis Reviews, 2019)

Ottowia flava sp. nov., isolated from fish intestines - Song-Biao Shi; Gui-Ding Li; Li-Fang Yang; Cong Liu; Ming-Guo Jiang; Qin-Yuan Li; Jia-Fa Wu; Kun Zhang; Long-Qian Jiang; Nai-Kun Shen; Cheng-Lin Jiang; Yi Jiang (Antonie van Leeuwenhoek, 2019)

Taxonomy of the order Mononegavirales: update 2019 - Gaya K. Amarasinghe; María A. Ayllón; Yīmíng Bào; Christopher F. Basler; Sina Bavari; Kim R. Blasdell; Thomas Briese; Paul A. Brown; Alexander Bukreyev; Anne Balkema-Buschmann; Ursula J. Buchholz; Camila Chabi-Jesus; et al. (Archives of Virology, 2019)

Modeling Alzheimer’s Disease by Induced Pluripotent Stem Cells Carrying APP D678H Mutation - Kuo-Hsuan Chang; Guey-Jen Lee-Chen; Ching-Chang Huang; Jia-Li Lin; Yi-Jing Chen; Pei-Chi Wei; Yen-Shi Lo; Chin-Fa Yao; Ming-Wei Kuo; Chiung-Mei Chen (Molecular Neurobiology, 2019)

Influence of permeation effect on the microfabric of the slip zone soils: A case study from the Huangtupo landslide - Fa-sheng Miao; Yi-ping Wu; Yuan-hua Xie; Lin-wei Li; Jie Li; Lei Huang (Journal of Mountain Science, 2019)

Portable vertical pendulum tiltmeter development and application test - Jie-ning Xia; Qiang Lin; Li-Xia Geng; Zhen Li; Song Luo; Nong-Fa Li; Jian-Feng Yu; Jun Liu (Acta Geodaetica et Geophysica, 2019)

Taxonomy of the order Mononegavirales: second update 2018 - Piet Maes; Gaya K. Amarasinghe; María A. Ayllón; Christopher F. Basler; Sina Bavari; Kim R. Blasdell; Thomas Briese; Paul A. Brown; Alexander Bukreyev; Anne Balkema-Buschmann; Ursula J. Buchholz; Kartik Chandran; et al. (Archives of Virology, 2019)

Numerical assessments of recharge-dominated groundwater flow and transport in the nearshore reclamation area in western Taiwan - Chuen-Fa Ni; Wei-Ci Li; Shaohua Marko Hsu; I-Hsien Lee; Chi-Ping Lin (Environmental Monitoring and Assessment, 2019)

Taxonomy of the order Mononegavirales: update 2018 - Gaya K. Amarasinghe; Nidia G. Aréchiga Ceballos; Ashley C. Banyard; Christopher F. Basler; Sina Bavari; Andrew J. Bennett; Kim R. Blasdell; Thomas Briese; Alexander Bukreyev; Yíngyún Caì; Charles H. Calisher; Cristine Campos Lawson; et al. (Archives of Virology, 2018)

Problems of classification in the family Paramyxoviridae - Bert Rima; Peter Collins; Andrew Easton; Ron Fouchier; Gael Kurath; Robert A. Lamb; Benhur Lee; Andrea Maisner; Paul Rota; Lin-Fa Wang (Archives of Virology, 2018)

Effect of dietary phospholipid levels on growth, lipid metabolism, and antioxidative status of juvenile hybrid snakehead (Channa argus×Channa maculata) - Shi-Mei Lin; Fa-Jian Li; Bundit Yuangsoi; Sompong Doolgindachbaporn (Fish Physiology and Biochemistry, 2018)

ACOS5 is required for primexine formation and exine pattern formation during microsporogenesis in Arabidopsis - Hui-hui Xie; Lin Chen; Fa-qing Xu; Wan-sheng Guo; Shui Wang; Zhong-nan Yang; Sen Zhang (Journal of Plant Biology, 2017)

Taxonomy of the order Mononegavirales: update 2017 - Gaya K. Amarasinghe; Yīmíng Bào; Christopher F. Basler; Sina Bavari; Martin Beer; Nicolás Bejerman; Kim R. Blasdell; Alisa Bochnowski; Thomas Briese; Alexander Bukreyev; Charles H. Calisher; Kartik Chandran; et al. (Archives of Virology, 2017)

Associations Between Hepatic Functions and Plasma Amyloid-Beta Levels—Implications for the Capacity of Liver in Peripheral Amyloid-Beta Clearance - Ye-Ran Wang; Qing-Hua Wang; Tao Zhang; Yu-Hui Liu; Xiu-Qing Yao; Fan Zeng; Jing Li; Fa-Yin Zhou; Lin Wang; Jia-Chuan Yan; Hua-Dong Zhou; Yan-Jiang Wang (Molecular Neurobiology, 2017)

Morphology and controlling factors of the longitudinal profile of gullies in the Yuanmou dry-hot valley - Lin Ding; Fa-chao Qin; Hai-dong Fang; Hui Liu; Bin Zhang; Cheng-qiang Shu; Qing-chun Deng; Gang-cai Liu; Qian-qian Yang (Journal of Mountain Science, 2017)

Alterations to biological soil crusts with alpine meadow retrogressive succession affect seeds germination of three plant species - Yi-kang Li; Jing-zheng Ouyang; Li Lin; Xing-liang Xu; Fa-wei Zhang; Yan-gong Du; Shu-li Liu; Guang-min Cao; Fa Han (Journal of Mountain Science, 2016)

Distribution of soil carbon in different grassland types of the Qinghai-Tibetan Plateau - Shu-li Liu; Yan-gong Du; Fa-wei Zhang; Li Lin; Yi-kang Li; Xiao-wei Guo; Qian Li; Guang-min Cao (Journal of Mountain Science, 2016)

Dietary lipid concentrations influence growth, liver oxidative stress, and serum metabolites of juvenile hybrid snakehead (Channa argus × Channa maculata) - Peng-Fei Zhao; Fa-Jian Li; Xiao-Ru Chen; Yong-Jun Chen; Shi-Mei Lin; Lu Zhang; Yun Li (Aquaculture International, 2016)

Taxonomy of the order Mononegavirales: update 2016 - Claudio L. Afonso; Gaya K. Amarasinghe; Krisztián Bányai; Yīmíng Bào; Christopher F. Basler; Sina Bavari; Nicolás Bejerman; Kim R. Blasdell; François-Xavier Briand; Thomas Briese; Alexander Bukreyev; Charles H. Calisher; et al. (Archives of Virology, 2016)

A novel process for obtaining pinosylvin using combinatorial bioengineering in Escherichia coli - Jing-long Liang; Li-qiong Guo; Jun-fang Lin; Ze-qi He; Fa-ji Cai; Jun-fei Chen (World Journal of Microbiology and Biotechnology, 2016)

Erratum to: Injection of Aβ1-40 into hippocampus induced cognitive lesion associated with neuronal apoptosis and multiple gene expressions in the tree shrew - Na Lin; Liu-Lin Xiong; Rong-ping Zhang; Hong Zheng; Lei Wang; Zhong-Yi Qian; Piao Zhang; Zhi-wei Chen; Fa-Bao Gao; Ting-Hua Wang (Apoptosis, 2016)

Injection of Aβ1-40 into hippocampus induced cognitive lesion associated with neuronal apoptosis and multiple gene expressions in the tree shrew - Na Lin; Liu-Lin Xiong; Rong-ping Zhang; Hong Zheng; Lei Wang; Zhong-Yi Qian; Piao Zhang; Zhi-wei Chen; Fa-Bao Gao; Ting-Hua Wang (Apoptosis, 2016)

Wide-angle incidence and P-wave transmission - Jun-Fa Xie; Cheng-Yu Sun; Mei-Yan Lin; Jing-Jing Li (Applied Geophysics, 2015)

Crack propagation patterns and energy evolution rules of coal within slotting disturbed zone under various lateral pressure coefficients - Lin Bai-quan; Liu Ting; Zou Quan-le; Zhu Chuan-jie; Yan Fa-zhi; Zhang Zhen (Arabian Journal of Geosciences, 2015)

Endoplasmic Reticulum Protein 29 Protects Axotomized Neurons from Apoptosis and Promotes Neuronal Regeneration Associated with Erk Signal - Yun-Hui Zhang; Visar Belegu; Yu Zou; Fang Wang; Bao-Jiang Qian; Ran Liu; Ping Dai; Wei Zhao; Fa-Bao Gao; Lei Wang; Li-Mei Cao; John W. McDonald; et al. (Molecular Neurobiology, 2015)

Characterization and Expression of Chicken Selenoprotein U - Yun-Yun Jiang; Jia-Qiang Huang; Gao-Chao Lin; Hui-Yuan Guo; Fa-Zheng Ren; Hao Zhang (Biological Trace Element Research, 2015)

TLR1 expression in mouse brain was increased in a KA-induced seizure model - Fa-Xiang Wang; Shi-Yong Liu; Xin Zheng; Xin Chen; Lin-Xiang Lu; Bin Chen; Xiao-yi Xiong; Hai-Feng Shu; Qing-Wu Yang; Hui Yang (Inflammation Research, 2015)

Quercetin induces mitochondrial-derived apoptosis via reactive oxygen species-mediated ERK activation in HL-60 leukemia cells and xenograft - Wei-Jiunn Lee; Michael Hsiao; Junn-Liang Chang; Shun-Fa Yang; Tsui-Hwa Tseng; Chao-Wen Cheng; Jyh-Ming Chow; Ke-Hsun Lin; Yung-Wei Lin; Chung-Chi Liu; Liang-Ming Lee; Ming-Hsien Chien (Archives of Toxicology, 2015)

Induction of plant virus defense response by brassinosteroids and brassinosteroid signaling in Arabidopsis thaliana - Da-Wei Zhang; Xing-Guang Deng; Fa-Qiong Fu; Hong-Hui Lin (Planta, 2015)

Non-alcoholic fatty liver disease and risk of in-stent restenosis after bare metal stenting in native coronary arteries - Ke-Qing Shi; Fa-Ling Wu; Wen-Yue Liu; Chen-Chen Zhao; Chang-Xi Chen; Yao-Yao Xie; Sheng-Jie Wu; Xian-Feng Lin; Yong-Ping Chen; Danny Ka-Ho Wong; Man-Fung Yuen; Ming-Hua Zheng (Molecular Biology Reports, 2014)

Increased risk of colorectal malignant neoplasm in patients with nonalcoholic fatty liver disease: a large study - Xian-Feng Lin; Ke-Qing Shi; Jie You; Wen-Yue Liu; Ying-Wan Luo; Fa-Ling Wu; Yong-Ping Chen; Danny Ka-Ho Wong; Man-Fung Yuen; Ming-Hua Zheng (Molecular Biology Reports, 2014)

Construction of an integrative linkage map and QTL mapping of grain yield-related traits using three related wheat RIL populations - Fa Cui; Chunhua Zhao; Anming Ding; Jun Li; Lin Wang; Xingfeng Li; Yinguang Bao; Junming Li; Honggang Wang (Theoretical and Applied Genetics, 2014)

Accumulation of mercury in rice grain and cabbage grown on representative Chinese soils - Chun-fa Liu; Cheng-xian Wu; Muhammad T. Rafiq; Rukhsanda Aziz; Dan-di Hou; Zhe-li Ding; Zi-wen Lin; Lin-jun Lou; Yuan-yuan Feng; Ting-qiang Li; Xiao-e Yang (Journal of Zhejiang University-SCIENCE B, 2013)

Selenium Attenuates High Glucose-Induced ROS/TLR-4 Involved Apoptosis of Rat Cardiomyocyte - Zhong-Wei Liu; Hai-Tao Zhu; Kun-Lun Chen; Chuan Qiu; Kai-Fa Tang; Xiao-Lin Niu (Biological Trace Element Research, 2013)

Nyamiviridae: Proposal for a new family in the order Mononegavirales - Jens H. Kuhn; Sadia Bekal; Yíngyún Caì; Anna N. Clawson; Leslie L. Domier; Marieke Herrel; Peter B. Jahrling; Hideki Kondo; Kris N. Lambert; Kathie A. Mihindukulasuriya; Norbert Nowotny; Sheli R. Radoshitzky; et al. (Archives of Virology, 2013)

Conditional and unconditional QTL mapping of drought-tolerance-related traits of wheat seedling using two related RIL populations - HONG ZHANG; FA CUI; LIN WANG; JUN LI; ANMING DING; CHUNHUA ZHAO; YINGUANG BAO; QIUPING YANG; HONGGANG WANG (Journal of Genetics, 2013)

Spatial patterns and climate drivers of carbon fluxes in terrestrial ecosystems of China - Gui‐Rui Yu; Xian‐Jin Zhu; Yu‐Ling Fu; Hong‐Lin He; Qiu‐Feng Wang; Xue‐Fa Wen; Xuan‐Ran Li; Lei‐Ming Zhang; Li Zhang; Wen Su; Sheng‐Gong Li; Xiao‐Min Sun; et al. (Global Change Biology, 2013)
Understanding the dynamics and underlying mechanism of carbon exchange between terrestrial ecosystems and the atmosphere is one of the key issues in global change research. In this study, we quantified the carbon fluxes in different terrestrial ecosystems in China, and analyzed their spatial variation and environmental drivers based on the long‐term observation data of China FLUX sites and the published data from other flux sites in China. The results indicate that gross ecosystem productivity ( GEP ), ecosystem respiration ( ER ), and net ecosystem productivity ( NEP ) of terrestrial ecosystems in China showed a significantly latitudinal pattern, declining linearly with the increase of latitude. However, GEP , ER , and NEP did not present a clear longitudinal pattern. The carbon sink functional areas of terrestrial ecosystems in China were mainly located in the subtropical and temperate forests, coastal wetlands in eastern China, the temperate meadow steppe in the northeast China, and the alpine meadow in eastern edge of Qinghai‐Tibetan Plateau. The forest ecosystems had stronger carbon sink than grassland ecosystems. The spatial patterns of GEP and ER in China were mainly determined by mean annual precipitation ( MAP ) and mean annual temperature ( MAT ), whereas the spatial variation in NEP was largely explained by MAT . The combined effects of MAT and MAP explained 79%, 62%, and 66% of the spatial variations in GEP , ER , and NEP , respectively. The GEP , ER , and NEP in different ecosystems in China exhibited ‘positive coupling correlation’ in their spatial patterns. Both ER and NEP were significantly correlated with GEP , with 68% of the per‐unit GEP contributed to ER and 29% to NEP . MAT and MAP affected the spatial patterns of ER and NEP mainly by their direct effects on the spatial pattern of GEP .

Metabolic Changes Detected by Ex Vivo High Resolution 1H NMR Spectroscopy in the Striatum of 6-OHDA-Induced Parkinson’s Rat - Hong-Chang Gao; Huan Zhu; Cai-Yong Song; Li Lin; Yun Xiang; Zhi-Han Yan; Guang-Hui Bai; Fa-Qing Ye; Xiao-Kun Li (Molecular Neurobiology, 2013)

Tectonic mechanism of the Suining (Ms5.0) earthquake, center of Sichuan Basin, China - Rong-jun Zhou; Yong Li; Laurence Svirchev; Yong-jiu Zhang; Deng-fa He; Yu-lin He; Pei-lin Zhao; Zan-jun Wang; Feng Long; Jin-rong Su; Shi-yuan Wang; Ming-jian Liang; et al. (Journal of Mountain Science, 2013)

A New Elasto-Viscoplastic Damage Model Combined with the Generalized Hoek–Brown Failure Criterion for Bedded Rock Salt and its Application - Lin-jian Ma; Xin-yu Liu; Qin Fang; Hong-fa Xu; Hui-min Xia; Er-bing Li; Shi-gang Yang; Wen-pei Li (Rock Mechanics and Rock Engineering, 2013)

Alpha-momorcharin, a RIP produced by bitter melon, enhances defense response in tobacco plants against diverse plant viruses and shows antifungal activity in vitro - Feng Zhu; Ping Zhang; Yan-Fa Meng; Fei Xu; Da-Wei Zhang; Jian Cheng; Hong-Hui Lin; De-Hui Xi (Planta, 2013)

Cathepsin B SNPs elevate the pathological development of oral cancer and raise the susceptibility to carcinogen-mediated oral cancer - Mu-Kuan Chen; Shih-Chi Su; Chiao-Wen Lin; Chiung-Man Tsai; Shun-Fa Yang; Chia-Jui Weng (Human Genetics, 2012)

Conditional QTL mapping of protein content in wheat with respect to grain yield and its components - LIN WANG; FA CUI; JINPING WANG; LI JUN; ANMING DING; CHUNHUA ZHAO; XINGFENG LI; DESHUN FENG; JURONG GAO; HONGGANG WANG (Journal of Genetics, 2012)

Impact of MCP-1 and CCR-2 gene polymorphisms on coronary artery disease susceptibility - Hsiu-Ling Lin; Kwo-Chang Ueng; Yih-Shou Hsieh; Whei-Ling Chiang; Shun-Fa Yang; Shu-Chen Chu (Molecular Biology Reports, 2012)

Landslides and catchment sedimentation in the Ta-Chia River influenced by the 1999 Taiwan Chi-Chi earthquake - Keh-Jian Shou; Li-Yuan Fei; Jiin-Fa Lee; Cheng-Yueh Wei; Sheng-Tsi Huang; You-Chang Lin (International Journal of Remote Sensing, 2012)

Antigen capture ELISA system for henipaviruses using polyclonal antibodies obtained by DNA immunization - Yoshihiro Kaku; Akira Noguchi; Glenn A. Marsh; Jennifer A. Barr; Akiko Okutani; Kozue Hotta; Boldbaatar Bazartseren; Christopher C. Broder; Akio Yamada; Satoshi Inoue; Lin-Fa Wang (Archives of Virology, 2012)

Study on synthesis of thalidomide analogues and their bioactivities; inhibition on iNOS pathway and cytotoxic effects - Chao-Bin Yeh; Pen-Yuan Lin; Jin-Ming Hwang; Chi-Jung Su; Ying-Tung Yeh; Shun-Fa Yang; Ming-Chih Chou (Medicinal Chemistry Research, 2012)

QTL detection of seven spike-related traits and their genetic correlations in wheat using two related RIL populations - Fa Cui; Anming Ding; Jun Li; Chunhua Zhao; Lin Wang; Xiuqin Wang; Xiaolei Qi; Xingfeng Li; Guoyu Li; Jurong Gao; Honggang Wang (Euphytica, 2012)

Physiological response of Cu and Cu mine tailing remediation of Paulownia fortunei (Seem) Hemsl - Zao-Fa Jiang; Su-Zhen Huang; Yu-Lin Han; Jiu-Zhou Zhao; Jia-Jia Fu (Ecotoxicology, 2012)

Dew water isotopic ratios and their relationships to ecosystem water pools and fluxes in a cropland and a grassland in China - Xue-Fa Wen; Xuhui Lee; Xiao-Min Sun; Jian-Lin Wang; Zhong-Min Hu; Sheng-Gong Li; Gui-Rui Yu (Oecologia, 2012)

QTL detection of seven quality traits in wheat using two related recombinant inbred line populations - Jun Li; Fa Cui; An-ming Ding; Chun-hua Zhao; Xiu-qin Wang; Lin Wang; Yin-guang Bao; Xiao-lei Qi; Xing-feng Li; Ju-rong Gao; De-shun Feng; Hong-gang Wang (Euphytica, 2012)

Wheat kernel dimensions: how do they contribute to kernel weight at an individual QTL level? - FA CUI; ANMING DING; JUN LI; CHUNHUA ZHAO; XINGFENG LI; DESHUN FENG; XIUQIN WANG; LIN WANG; JURONG GAO; HONGGANG WANG (Journal of Genetics, 2011)

Molecular and morphological evidences reveal a cryptic species in the Vinaceous Rosefinch Carpodacus vinaceus (Fringillidae; Aves) - Hsu‐Chun Wu; Rong‐Chien Lin; Hsin‐Yi Hung; Chia‐Fen Yeh; Jui‐Hua Chu; Xiao‐Jun Yang; Chiou‐Ju Yao; Fa‐Sheng Zou; Cheng‐Te Yao; Shou‐Hsien Li; Fu‐Min Lei (Zoologica Scripta, 2011)
Wu, H.‐C., Lin, R.‐C., Hung, H.‐Y., Yeh, C.‐F., Chu, J.‐H., Yang, X.‐J., Yao, C.‐J., Zou, F.‐S., Yao, C.‐T., Li, S.‐H. & Lei, F.‐M. (2011). Molecular and morphological evidences reveal a cryptic species in the Vinaceous Rosefinch Carpodacus vinaceus (Fringillidae; Aves). — Zoologica Scripta, 40 , 468–478. The Vinaceous Rosefinch ( Carpodacus vinaceus ) is endemic in East Asia with two recognized subspecies – C. v. vinaceus , distributed along the eastern edge of the Tibetan Plateau and the Himalayas, and C. v. formosanus , restricted to Taiwan’s Central Mountain Range. As reflected in a controversial taxonomic history, this vastly disjunctive distribution pattern suggests that the subspecies, having been isolated from each other for a long time, might have diverged, challenging the current taxonomic treatment and calling for possible species delimitation. Sequences of two mitochondrial fragments (mtDNA) and two Z‐linked nuclear loci (zDNA) were used to reconstruct the intraspecific phylogeny of C. vinaceous . The mtDNA tree shows that the two subspecies of the vinaceous rosefinch form two exclusively monophyletic clades. All but one zDNA sequences from the nominate subspecies and C. v. formosanus also formed exclusively monophyletic clades (the exceptional zDNA sequence from C. v. vinaceous formed a weakly supported clade with two outgroup species). Moreover, by conducting quantitative comparisons of morphometric traits and male plumage coloration, we found that the two subspecies exhibit distinguishable morphological differences. All the evidence therefore suggests that C. v. formosanus is a cryptic species and that its taxonomic status should be restored to full species. Molecular dating suggests that the two sibling rosefinches split 1.7 ± 0.2 million years ago, providing a point estimate for the historical connectivity of biota between eastern Tibet‐Himalayas and montane Taiwan.

Expression patterns of prion protein gene in differential genotypes sheep: quantification using molecular beacon real-time RT-PCR - Chuan Wang; Run Wu; Fa-Di Li; Lei Liu; Xiao-Li Zhang; Chun-Lin Zhao; Xiao-Long Diao; Hong-Wei Guan (Virus Genes, 2011)

Conditional QTL mapping for plant height with respect to the length of the spike and internode in two mapping populations of wheat - Fa Cui; Jun Li; Anming Ding; Chunhua Zhao; Lin Wang; Xiuqin Wang; Sishen Li; Yinguang Bao; Xingfeng Li; Deshun Feng; Lingrang Kong; Honggang Wang (Theoretical and Applied Genetics, 2011)

Arbuscular mycorrhizal fungal community structure and diversity in response to long-term fertilization: a field case from China - Fa Yuan Wang; Jun Li Hu; Xian Gui Lin; Sheng Wu Qin; Jun Hua Wang (World Journal of Microbiology and Biotechnology, 2011)

Ecotoxicity assessment of aged petroleum sludge using a suite of effects-based end points in earthworm Eisenia fetida - Shi-Jie Wang; Zeng-Guang Yan; Guan-Lin Guo; Gui-Lan Lu; Qun-Hui Wang; Fa-Sheng Li (Environmental Monitoring and Assessment, 2010)

Angiotensin-converting enzyme 2 (ACE2) proteins of different bat species confer variable susceptibility to SARS-CoV entry - Yuxuan Hou; Cheng Peng; Meng Yu; Yan Li; Zhenggang Han; Fang Li; Lin-Fa Wang; Zhengli Shi (Archives of Virology, 2010)

Interspecific hybrids between Chrysanthemum grandiflorum (Ramat.) Kitamura and C. indicum (L.) Des Moul. and their drought tolerance evaluation - Chun-Qing Sun; Fa-Di Chen; Nian-Jun Teng; Zhao-Lei Liu; Wei-Min Fang; Xi-Lin Hou (Euphytica, 2010)

Modeling air gun signatures in marine seismic exploration considering multiple physical factors - Guo-Fa Li; Ming-Qiang Cao; Hao-Lin Chen; Cheng-Zhou Ni (Applied Geophysics, 2010)

Immunoglobulin heavy chain diversity in Pteropid bats: evidence for a diverse and highly specific antigen binding repertoire - Michelle L. Baker; Mary Tachedjian; Lin-Fa Wang (Immunogenetics, 2010)

Factors affecting seed set in the crosses between Dendranthema grandiflorum (Ramat.) Kitamura and its wild species - Chun-Qing Sun; Fa-Di Chen; Nian-Jun Teng; Zhao-Lei Liu; Wei-Min Fang; Xi-Lin Hou (Euphytica, 2010)

Provenance and thermal history of the Bayan Har Group in the western‐central Songpan–Ganzi–Bayan Har terrane: Implications for tectonic evolution of the northern Tibetan Plateau - Guo‐Can Wang; Robert P. Wintsch; John I. Garver; Mary Roden‐Tice; She‐Fa Chen; Ke‐Xin Zhang; Qi‐Xiang Lin; Yun‐Hai Zhu; Shu‐Yuan Xiang; De‐Wei Li (Island Arc, 2009)
Triassic turbidites dominate the Songpan–Ganzi–Bayan Har (SGBH) terrane of the northern Tibetan Plateau. U‐Pb dating on single detrital zircon grains from the Triassic Bayan Har Group turbidites yield peaks at 400–500 m.y., 900–1000 m.y., 1800–1900 m.y., and 2400–2500 m.y., These results are consistent with recently published U‐Pb zircon ages of pre‐Triassic bedrock in the East Kunlun, Altyn, Qaidam, Qilian and Alaxa areas to the north, suggesting that provenance of the Bayan Har Group may include these rocks. The similarities in the compositions of the lithic arkosic sandstones of the Bayan Har Group with the sandstones of the Lower‐Middle Triassic formations in the East Kunlun terrane to the north also suggests a common northern provenance for both. A well exposed angular unconformity between the Carboniferous–Middle Permian mélange sequences and the overlying Upper Permian or Triassic strata indicates that regional deformation occurred between the Middle and Late Permian. This deformation may have been the result of a soft collision between the Qiangtang terrane and the North China Plate and the closure of the Paleo‐Tethyan oceanic basin. The Bayan Har Group turbidites were then deposited in a re‐opened marine basin on a shelf environment. Fission‐track dating of detrital zircons from the Bayan Har Group sandstones revealed pre‐ and post‐depositional age components, suggesting that the temperatures did not reach the temperatures necessary to anneal retentive zircon fission tracks (250–300°C). A 282–292 m.y. peak age defined by low U concentration, retentive zircons likely reflects a northern granitic source. Euhedral zircons from two lithic arkoses with abundant volcanic fragments in the southern area yielded a ∼237 m.y. zircon fission track (ZFT) peak age, likely recording the maximum age of deposition. A dominant post‐depositional 170–185 m.y. ZFT peak age suggests peak temperatures were reached in the Early Jurassic. Some samples appear to record a younger thermal event at ∼140 m.y., a short lived event that apparently affected only the least retentive zircons.

Fluorescent co-localization of PTS1 and PTS2 and its application in analysis of the gene function and the peroxisomal dynamic in Magnaporthe oryzae - Jiao-yu Wang; Xiao-yan Wu; Zhen Zhang; Xin-fa Du; Rong-yao Chai; Xiao-hong Liu; Xue-qin Mao; Hai-ping Qiu; Yan-li Wang; Fu-cheng Lin; Guo-chang Sun (Journal of Zhejiang University-SCIENCE B, 2008)

Overexpression of the trehalose-6-phosphate phosphatase gene OsTPP1 confers stress tolerance in rice and results in the activation of stress responsive genes - Liang-Fa Ge; Dai-Yin Chao; Min Shi; Mei-Zhen Zhu; Ji-Ping Gao; Hong-Xuan Lin (Planta, 2008)

Mitochondrial anchoring of PKCα by PICK1 confers resistance to etoposide-induced apoptosis - Wei-Li Wang; Sheau-Farn Yeh; Eagle Yi-Kung Huang; Yu-Ling Lu; Chun-Fa Wang; Chi-Ying F. Huang; Wey-Jinq Lin (Apoptosis, 2007)

Expression of truncated phosphoproteins of Nipah virus and Hendra virus in Escherichia coli for the differentiation of henipavirus infections - Ji-Ming Chen; Koon Chu Yaiw; Meng Yu; Lin-Fa Wang; Qing-Hua Wang; Gary Crameri; Zhi-Liang Wang (Biotechnology Letters, 2007)

Changes of cell proliferation and differentiation in the developing brain of mouse - Lin Qiu; Chang-Lian Zhu; Xiao-Yang Wang; Fa-Lin Xu (Neuroscience Bulletin, 2007)

Assessing Impacts of Typhoons and the Chi-Chi Earthquake on Chenyulan Watershed Landscape Pattern in Central Taiwan Using Landscape Metrics - Yu-pin Lin; Tsun-kuo Chang; Chen-fa Wu; Te-chih Chiang; Shin-hwei Lin (Environmental Management, 2006)

Peptide mimotopes of phomopsins: Identification, characterization and application in an immunoassay - Meng Yu; Khin Than; Steve Colegate; Brian Shiell; Wojtek P. Michalski; Stephen Prowse; Lin-Fa Wang (Molecular Diversity, 2005)

The July 14, 2003 Qianjiangping landslide, Three Gorges Reservoir, China - Fa-Wu Wang; Ye-Ming Zhang; Zhi-Tao Huo; Tatsunori Matsumoto; Bo-Lin Huang (Landslides, 2004)

Arbuscular mycorrhizal status of wild plants in saline-alkaline soils of the Yellow River Delta - Jian-Min Zhou; Xian-Gui Lin; Fa-Yuan Wang; Run-Jin Liu (Mycorrhiza, 2004)

Identification of two chilling-regulated 1-aminocyclopropane- 1-carboxylate synthase genes from citrus (Citrus sinensis Osbeck) fruit - Wai Shing Wong; Wen Ning; Pei Lin Xu; Shain Dow Kung; Shang Fa Yang; Ning Li (Plant Molecular Biology, 1999)